2016
DOI: 10.18632/oncotarget.11308
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of sodium fluoride on cultured splenic lymphocyte proliferation in mice

Abstract: Fluoride-induced immunotoxicity has been documented in vivo, but limited reports have focused on the effects of fluoride on lymphocytes in vitro. Therefore, we have examined the suppressive effects of sodium fluoride on cultured splenic lymphocytes in mice. CD3+ T lymphocytes, CD19+ B lymphocytes, cytokines, and cell-cycle markers were analyzed through the use of a cell-counting kit, western blot, and flow cytometery. Splenic lymphocytes were isolated from 3-week-old male ICR mice and exposed to sodium fluorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…We also measured the Th17 and found that IL-17A content was decreased after exposure to NaF. In our previous study, we found that high fluoride levels can reduce IL-2, IL-4, IL-6, TNF-α and IFN-γ in the cecal tonsil, and intestines of broiler chickens [ 14 ], and that NaF can reduce the percentages of CD3 + , CD3 + CD4 + , CD3 + CD8 + T lymphocytes and CD19 + B lymphocytes and of IL-2, TNF-α, IFN-γ, TGF-β expression levels in cultured splenic lymphocytes of mice [ 36 ]. Our findings are consistent with the report of Yin et al [ 43 ] that high fluoride decreased the percentages of thymic CD4 + , CD8 + T cells and IL-2, IL-10 mRNA expression in mice.…”
Section: Discussionmentioning
confidence: 99%
“…We also measured the Th17 and found that IL-17A content was decreased after exposure to NaF. In our previous study, we found that high fluoride levels can reduce IL-2, IL-4, IL-6, TNF-α and IFN-γ in the cecal tonsil, and intestines of broiler chickens [ 14 ], and that NaF can reduce the percentages of CD3 + , CD3 + CD4 + , CD3 + CD8 + T lymphocytes and CD19 + B lymphocytes and of IL-2, TNF-α, IFN-γ, TGF-β expression levels in cultured splenic lymphocytes of mice [ 36 ]. Our findings are consistent with the report of Yin et al [ 43 ] that high fluoride decreased the percentages of thymic CD4 + , CD8 + T cells and IL-2, IL-10 mRNA expression in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis is one early sign of genotoxic damage in mature testis, and plays critical roles in spermatozoa. Fluoride harbors various cellular effects and excessive fluoride may cause oxidative stress, inhibit protein secretion and transport [ 7 , 8 ], induce inflammatory response [ 9 , 10 ], and interfere with cell proliferation and migration which could be fluoride concentration and/or cell type dependent [ 8 , 11 , 12 ]. However, the underlying mechanisms of these cellular functions are less clear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that excessive ingestion of fluoride can results in structural and functional changes in teeth and bones, such as mottling of teeth or skeletal fluorosis [ 6 9 ]. And along with teeth or skeletal fluorosis, pathological changes have also been reported in soft tissues including thyroid [ 10 ], thymus [ 11 ], brain [ 12 , 13 ], heart [ 14 , 15 ], liver [ 16 – 18 ], spleen [ 19 22 ], gastro-intestinal tract [ 23 , 24 ], cecal tonsil [ 25 , 26 ], bursa of Fabricius [ 27 ] and reproductive organs [ 28 ]. As the primary organ concerned with excretion and retention of fluoride, kidney is quite sensitive to the toxicity of fluoride [ 29 ].…”
Section: Introductionmentioning
confidence: 99%